The Emerging Roles of Pericytes in Modulating Tumor Microenvironment - Sun, Ruipu; Kong, Xiangzhan; Qiu, Xiaoyi; Huang, Cheng; Wong, Ping-Pui (Frontiers in Cell and Developmental Biology, 2021)
Pericytes (PCs), known as mural cells, play an important blood vessel (BV) supporting role in regulating vascular stabilization, permeability and blood flow in microcirculation as well as blood brain barrier. In carcinogenesis, defective interaction between pericytes and endothelial cells contributes to the formation of leaky, chaotic and dysfunctional vasculature in tumors. However, recent works from other laboratories and our own demonstrate that the direct interaction between pericytes and other stromal cells/cancer cells can modulate tumor microenvironment to favor cancer growth and progression, independent of its BV supporting role. Furthermore, accumulating evidence suggest that pericytes have an immunomodulatory role. In the current review, we focus on recent advancement of the understanding of PC’s regulatory role in the tumor microenvironment by communicating with endothelial cells (ECs), immune cells, and tumor cells, and discuss how we can target pericyte’s functions to re-model tumor microenvironment for an improved cancer treatment strategy.